Efficient biosynthesis of heterodimeric C3-aryl pyrroloindoline alkaloids - Wenya Tian (Nature Portfolio, 2018)
The hexahydropyrrolo[2, 3-b]indole (HPI) framework is found in many natural products. Here, the authors discover a P450 enzyme and develop a whole-cell biocatalysis system that produces the HPI naseseazine C (NAS-C) and 30 NAS-C analogs, several of which show neuroprotective properties.